2023
DOI: 10.21203/rs.3.rs-2575605/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Socioeconomic impacts of flooding and its coping strategies in Nigeria: Evidence from Dagiri community, Gwagwalada area council of Abuja

Abstract: Dagiri, a community in the Gwagwalada area council, has been ravaged by floods. The most recent which took place on 25th July 2020 was devastating and had severe impacts on the community. This study focuses on the socioeconomic implication of the 2020 flood in the Dagari community. To achieve the specific objectives, a number of methodologies were employed such as map analysis, questionnaire survey, oral interviews, and site observations. Presentation of results was done using percentages, tables, bar graphs, … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
2
2
0
Order By: Relevance
“…This might contribute to their level of productivity and ability to be more creative in tourist enterprise. The result was in line with the findings of Badamosi et al (2023) and Adegoroye et al (2024). It was revealed that about 11.1% of them were below 20 years, 37.1% of them were between age 20 and 29 years and 22.2% of them were within the age bracket of 30 -39 years.…”
Section: Results and Discussion Demographic Profiles Of The Respondentssupporting
confidence: 92%
“…This might contribute to their level of productivity and ability to be more creative in tourist enterprise. The result was in line with the findings of Badamosi et al (2023) and Adegoroye et al (2024). It was revealed that about 11.1% of them were below 20 years, 37.1% of them were between age 20 and 29 years and 22.2% of them were within the age bracket of 30 -39 years.…”
Section: Results and Discussion Demographic Profiles Of The Respondentssupporting
confidence: 92%
“…Of the remaining respondents, approximately 13.86% were not married, 1.43% were divorced. The results are in line with the studies of Adegoroye et al (2021) [1] , Badamosi et al (2023) [5] and Oluwalade et al (2023a) [14] who reported that married households are the majority in the area. The household heads ' educational level in particular is an important quantity that can influence the household solid waste social control activity (Oladosu et al, 2024) [10] .…”
Section: Demographic Features Of the Sampled Respondentssupporting
confidence: 92%
“…The implication of this is that farmers in the study area are mature and can effectively take crucial decisions jointly with their spouses. This will also afford them the opportunity to get family labour to be used on the farm [18,36,37,38]. The results also indicated that the majority (90.7%) of the FBS participants had at least primary school education while about 88.7% of the nonparticipants had at least primary school education.…”
Section: Propensity Score Matchingmentioning
confidence: 96%
“…The annual average temperature is 26.9°C. The average yearly precipitation is 1,165.0 mm [17,18]. Nigeria has rain all year round, with April through October seeing the most precipitation and November to March seeing very little [17].…”
Section: Study Areamentioning
confidence: 99%